Moderate white light exposure enhanced spatial memory retrieval by activating a central amygdala-involved circuit in mice - MengJuan Shang; MeiLun Shen; RuoTong Xu; JingYu Du; JiMeng Zhang; Ding OuYang; JunZe Du; JunFeng Hu; ZhiChuan Sun; BingXia Wang; Qian Han; Yang Hu; et al. (Communications Biology, 2023)
Abstract Light exposure can profoundly affect neurological functions and behaviors. Here, we show that short-term exposure to moderate (400 lux) white light during Y-maze test promoted spatial memory retrieval and induced only mild anxiety in mice. This beneficial effect involves the activation of a circuit including neurons in the central amygdala (CeA), locus coeruleus (LC), and dentate gyrus (DG). Specifically, moderate light activated corticotropin-releasing hormone (CRH) positive (+) CeA neurons and induced the release of corticotropin-releasing factor (CRF) from their axon terminals ending in the LC. CRF then activated tyrosine hydroxylase-expressing LC neurons, which send projections to DG and release norepinephrine (NE). NE activated β-adrenergic receptors on CaMKIIα-expressing DG neurons, ultimately promoting spatial memory retrieval. Our study thus demonstrated a specific light scheme that can promote spatial memory without excessive stress, and unraveled the underlying CeA-LC-DG circuit and associated neurochemical mechanisms.